2007
DOI: 10.1016/j.ijsolstr.2006.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing energy input for fracture by analysis of the energy required to initiate dynamic mode I crack growth

Abstract: A problem for a central crack in a plate subjected to plane strain conditions is investigated. Mode I crack loading is created by a dynamic pressure pulse applied at large distance from the crack. It was found that for a certain combination of amplitude and duration of the pulse applied, energy transmitted to the sample has a strongly marked minimum, meaning that with the pulse amplitude or duration moving away from the optimal values minimum energy required for initiation of crack growth increases rapidly. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…The important feature of the incubation time fracture criterion is its capability to predict fracture initiation conditions with reliability and precision for quasi-static cases of relatively slowly changing loads and geometry as well as for dynamic cases of high-rate loads and fast changes in geometry (see, e.g. [9][10][11][12][13]). Moreover, the criterion is supplying a smooth transition between these two cases [11].…”
Section: Minimization Of Fracture Energymentioning
confidence: 99%
“…The important feature of the incubation time fracture criterion is its capability to predict fracture initiation conditions with reliability and precision for quasi-static cases of relatively slowly changing loads and geometry as well as for dynamic cases of high-rate loads and fast changes in geometry (see, e.g. [9][10][11][12][13]). Moreover, the criterion is supplying a smooth transition between these two cases [11].…”
Section: Minimization Of Fracture Energymentioning
confidence: 99%
“…Lately an approach making it possible to embed the ITFC into numerical computational schemes based on finite element method (FEM) was developed [12][13][14]. Utilizing this approach simulation of several different experiments on dynamic impact fracture caused by high-rate loads was performed [12,15].…”
Section: Bratovmentioning
confidence: 99%
“…[15] amount of energy sufficient to initiate propagation of a mode I loaded central crack was extensively explored. It was demonstrated that energy to input into media containing a crack in order to advance this crack does strongly depend on the shape of the load pulse applied.…”
Section: Optimization Of Energy Input In Industrial Processes Connectmentioning
confidence: 99%
“…For example for granite with initial cracks of 5 mm fractured by rectangular shaped load pulses, if the frequency of the fracturing impacts differs from the optimal one by 10%, energy cost of fracture creation is exceeding the minimal value by 12% [15]. Taking into consideration the fact that the efficiency of rupture connected processes rarely exceeds a few percent, it gets evident that even a possibility of small improvement of energy input is of a great importance for industry.…”
Section: Optimization Of Energy Input In Industrial Processes Connectmentioning
confidence: 99%